Alienation in the Plastic Arts: Ceramics as a Model - Al-Basha, Narmin Ramzi Qasim Mustafa; Al-Badran, Oras Jabbar Suhaim (South Asian Journal of Social Sciences and Humanities, 2023)
The current research is concerned with studying (alienation in the plastic arts (ceramics as a model), as alienation was studied in terms of its effect on the artist, which in turn had its effect on the artistic work in formation, to be spatial discrepancies and displacements whose vocabulary is mixed with oppositions, disruption, and displacement, which create an apparent formal defect according to the contemporary perspective, with The development of technology and technique. Alienation appeared to be found in form in the plastic arts in general, and one of these arts is ceramics. Alienation in ceramics broke the traditional pattern and transcended the vocabulary of work associated with intellectual and conceptual transformations that resulted in the elements of alienation, including the art schools that brought about a shift in the artist’s concepts toward rejection. Everything that is familiar and traditional, as the artist sought to search for the idea that is different from the concept through the influence of the potter, which was achieved as a result of communication between art and society, which gives renewed concepts to the idea to achieve alienation according to the transformations of ceramic art, and the idea from which the potter started and developed treatments for reality through research was adopted.